2020
DOI: 10.1038/s41598-020-78133-4
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated nucleophilic substitution reactions of dansyl chloride with aniline under ambient conditions via dual-tip reactive paper spray

Abstract: Paper spray ionization (PSI) mass spectrometry (MS) is an emerging tool for ambient reaction monitoring via microdroplet reaction acceleration. PSI-MS was used to accelerate and monitor the time course of the reaction of dansyl chloride with aniline, in acetonitrile, to produce dansyl aniline. Three distinct PSI arrangements were explored in this study representing alternative approaches for sample loading and interaction; conventional single tip as well as two novel setups, a dual-tip and a co-axial arrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Different approaches for paper sample loading, including the single‐tip, dual‐tip, and co‐axial, were tested to limit on‐paper interaction between the reagents. Nucleophilic substitution reaction to produce dansyl aniline from dansyl chloride and aniline was shown by using dual‐tip methods with the highest yield [47]. Moreover, different versions of ESI‐based spray shown in Figure 1A can be applied to paper spray [11].…”
Section: Hyphenated Microdroplet Ms Techniquesmentioning
confidence: 99%
“…Different approaches for paper sample loading, including the single‐tip, dual‐tip, and co‐axial, were tested to limit on‐paper interaction between the reagents. Nucleophilic substitution reaction to produce dansyl aniline from dansyl chloride and aniline was shown by using dual‐tip methods with the highest yield [47]. Moreover, different versions of ESI‐based spray shown in Figure 1A can be applied to paper spray [11].…”
Section: Hyphenated Microdroplet Ms Techniquesmentioning
confidence: 99%
“…Similarly, nanobubbles are becoming important in various aspects of environmental remediation . These experiments are mainly performed in electrospray sonic ionization, ,, nanoelectrospray ionization, , paper spray ionization, and individually levitated droplets . Furthermore, the Zare group found that such reactions can also be performed in colliding microdroplets formed from two ESI sources kept at an angle such that the spray plumes intersect each other. , Many microdroplet reactions were scaled up to prepare gram-scale quantities of products.…”
Section: Introductionmentioning
confidence: 99%
“…Microdroplet chemistry has been proven to fantastically accelerate many organic and biological reactions due to its confined and high-surface-area properties in recent years. Suzuki–Miyaura reactions have already been investigated by microdroplet chemistry in desorption electrospray ionization mass spectrometry (DESI-MS), , nanoelectrospray ionization mass spectrometry (nanoESI-MS), paper spray ionization mass spectrometry (PSI-MS), and sonic spray ionization . Paper spray ionization is a simple and low-cost technology to form two typical microdroplet formats, namely, thin film and sprayed charged droplets, to facilitate the synthesis and derivatization of targets in situ. In PSI, a small drop of reactants is pipetted on the paper surface, and the reactant solution rapidly forms a thin film on the surface along with the evaporation of the solvent, improving the reaction rate moderately. In addition, the reactants migrate to the paper tip and spray into charged micrometer droplets by applying a high voltage, further accelerating the reaction significantly .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the lack of easily ionized chemical groups, general brominated organic compounds are difficult to ionize by matrix-assisted laser desorption ionization (MALDI), electrospray ionization (ESI), paper spray ionization, and other ambient ionization sources, leading to low-sensitivity in MS analysis. With the benefits of low cost, no sample pretreatment, minimal matrix effect, and high analytical efficiency, PSI-MS has been commonly used in clinical diagnosis, environmental analysis, and reaction monitoring. ,, To improve the sensitivity of weakly polar and nonpolar substances by MS detection, online derivatization of the target analytes has been integrated into PSI (termed as reactive PSI). Huang’s group quantitatively determined quinones in complex samples by reactive PSI-MS, where quinones were in situ derivatized with cysteamine to significantly improve the ionization efficiency of quinones.…”
Section: Introductionmentioning
confidence: 99%